Best Practice Guidelines – DEGUM Recommendations on Breast Ultrasound - Vogel-Minea, Claudia Maria; Bader, Werner; Blohmer, Jens-Uwe; Duda, Volker; Eichler, Christian; Fallenberg, Eva; Farrokh, André; Golatta, Michael; Gruber, Ines; Hackelöer, Bernhard-Joachim; Heil, Jörg; Madjar, Helmut; Marzotko, Ellen; Merz, Eberhard; Mundinger, Alexander; Müller-Schimpfle, Markus; Ohlinger, Ralf; Peisker, Uwe; Schulz-Wendtland, Ruediger; Schäfer, Fritz KW; Solbach, Christine; Warm, Mathias; Watermann, Dirk; Wojcinski, Sebastian; Hahn, Markus (Ultraschall in der Medizin - European Journal of Ultrasound, 2025)
Breast ultrasound has been established for many years as an important method in addition to mammography for clarifying breast findings. The goal of the Best Practice Guidelines Part III of the DEGUM breast ultrasound working group is to provide colleagues working in senology with information regarding the specific medical indications for breast ultrasound in addition to the current ultrasound criteria and assessment categories published in part I and the additional and optional sonographic diagnostic methods described in part II. The value of breast ultrasound for specific indications including follow-up, evaluation of breast implants, diagnostic workup of dense breast tissue, diagnostic workup during pregnancy and lactation, and the diagnostic workup of breast findings in men is discussed. Each section after the general information section contains a description of specific pathologies followed by a short summary and DEGUM recommendations for the particular indications. The latest S3 guidelines and AGO guidelines were taken into consideration.Die Mammasonografie hat sich seit vielen Jahren neben der Mammografie als wichtige Methode zur Abklärung von Brustbefunden etabliert.Der Arbeitskreis Mammasonografie der DEGUM beabsichtigt mit der Best Practice Guideline – Teil III, den senologisch tätigen Kolleginnen und Kollegen – neben dem in Teil I publizierten aktuellen Dignitätskriterien- und Befundungskatalog und den in Teil II beschriebenen additiven und fakultativen sonografischen diagnostischen Methoden – im vorliegenden Teil III die speziellen medizinischen Indikationsbereiche der Mammasonografie zu erläutern. Es wird der Stellenwert der Mammasonografie in Indikationsbereichen wie in der Nachsorge, der Beurteilung von Brustimplantaten, Diagnostik bei dichtem Drüsenparenchym, Diagnostik in Schwangerschaft und während der Stillzeit sowie in der Diagnostik von Brustbefunden beim Mann behandelt. Nach allgemeinen Informationen beinhaltet jedes Kapitel einen Teil mit Beschreibung spezieller Pathologien und zum Abschluss in gewohnter Manier eine kurze Zusammenfassung sowie die DEGUM-Empfehlungen zum jeweiligen Indikationsbereich. Dabei wurden die neusten S3-LL und AGO-Guidelines berücksichtigt.
Keywords: breast; ultrasound; mammography; Gynecology; Radiology